The role of religion for an alternative sustainable governance theory - Malik, Maszlee (Versita, Warsaw, 2013)
In post-modern times, there has been much empirical evidence to indicate that religions and faiths play a pro-active role in the field of civil society but more importantly in the development of societies, which is a major factor in political and economic development of a country, as well as its governance. Accordingly, the contemporary reality of plurality demands a fresh look into the narratives of different civilisations, cultures and ideologies, rather than imposed meta-narratives of modernity. Hence, explorations of religion and faith to develop an alternative notion of “good governance” from “other’s” worldview are also necessary. Much could be learned from cultures, religions and faiths in the realm of governance studies from the phenomenological perspective. This paper is an attempt to explore how religion could play its functional role to create a sustainable governance concept based on values and ethics. It will look into the situation of religion at present, and how it fits into the framework of governance, and the arguments will be supported by examples and evidence of the viability of the relation between religion and governance.